Reformulation of Palm Oil Governance Regulations in Forest Areas Towards Legal and Ecological Justice in Indonesia - Siagian, Royan; Israhadi, Evita Isretno (Greenation Publisher & Yayasan Global Resarch National, 2025)
Ilegal oil palm plantations in forest areas are a serious challenge that threatens legal justice, environmental sustainability, and the well-being of local communities in Indonesia. This research is motivated by the rampant practice of transferring forest functions into oil palm land which often does not have a legal basis, especially in the Central Kalimantan region. The purpose of this study is to evaluate the implementation of law enforcement against illegal palm oil business actors, assess legal certainty based on the principle of justice, and formulate a more equitable legal reform model. The method used is empirical juridical research with legal, conceptual, and case approaches. The results of the study show that the implementation of Articles 110A and 110B of Law Number 6 of 2023 still faces various obstacles, such as overlapping authority, weak law enforcement capacity, and the influence of political and economic interests. Although normatively it has provided a basis for action, the regulation has not been able to realize substantive justice for the community and the environment. Theoretical analysis using the framework of Lawrence M. Friedman, John Rawls, and Jan Michiel Otto reveals the need for legal reform that is adaptive, participatory, and recognizes legal pluralism, including the recognition of customary law. In conclusion, the success of the reformulation of palm oil regulations is not enough with the tightening of administrative sanctions, but must be accompanied by institutional structuring, the use of monitoring technology, and the active involvement of local communities in the legal process. Policy recommendations are directed at the creation of socially and ecologically equitable palm oil governance through a collaborative approach between the state, communities, and business actors.